Principles of building a new ecosystem: Economic, legal and social aspects - Danilchenko S. L., Sudakova N. E., Kurdiumov A. V., Gromova N. S., Kruglov V. N., Astafurova O. A., Kulagina I. I., Malov M. S., Ushakova O. A., Kostenko E. G., Medvedeva N. V., Meshcheriagina V. A., Vilacheva M. N., Balkovaia V. G., Lankova V. A., Ponikarovskaya V. V., Paniushkina M. A., Kvasov V. B., Sizova A. S., Babushkin E. R., Semenova S. S. (Principles of building a new ecosystem: Economic, legal and social aspects, 2024)
the chapter is devoted to the problems of forming the national identity of modern Russian youth, which is defined as an important condition for increasing the level of legal culture of society. There has been a tendency towards a decrease in the general level of culture, an increase in infantilism, and the presence of gaps in the moral consciousness of a significant part of young people. According to the authors, without overcoming these negative aspects it is impossible to build a truly legal state and form a civil society. As a condition for increasing the legal culture of modern Russian society, a system of state-patriotic education is proposed, designed to develop a sense of national pride and professional responsibility.
Keywords: патриотизм; национальная идентичность; национальное самосознание; правовая культура; правосознание; legal consciousness; legal culture; Patriotism; national identity; государственно-патриотическое воспитание; state-patriotic education; правовая культура общества; правосознание молодежи; legal culture of society; legal consciousness of youth; national self-consciousness